PERAN KADER POSYANDU DALAM MENINGKATKAN STATUS GIZI ANAK STUNTING MELALUI PIJAT TUINA DAN PMBA CURUP TENGAH - ITA ZUBAIDA, YENNI PUSPITA; Andini, Indah Fitri; Febrina, Lydia; Esmiati, Farida; Utario, Yossy (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting must be a priority because its impact is very broad. Stunting has an impact on increasing the risk of morbidity and death, delayed motor development and hampered mental growth, increasing the risk of overweight and obesity, increasing the risk of degenerative diseases. The nutritional needs of toddlers will not be met if toddlers experience problems with eating and feeding children. One way to overcome this is through community service activities to empower posyandu cadres in the form of training to increase knowledge and skills in performing tuina massage and feeding babies and children. The target of the activity was 35 posyandu cadres in the District Work Area of Rejang Lebong in 2021. Training activities were carried out offline. The results of the participants' pretest and posttest showed an increase in knowledge of 27.0 and the results of the skills assessment using the checklist obtained an average score of 87. The community service activities by empowering posyandu cadres through training and mentoring can increase the knowledge and skills of posyandu cadres in carrying out tuina massage and IYCF.